UMP researchers produce antidandruff shampoo from herbal plant extracts - Nor Salwana, Mohammad Idris (2020)
Kuantan, 28 August 2020 - Problems with itchy scalp, dandruff and hair loss are often experienced by some people regardless of whether they are men or women.